Mechanisms of Herbal Nephroprotection in diabetes mellitus - Dorin Dragoș; Maria Mirabela Manea; Delia Timofte; Dorin Ionescu (Journal of Diabetes Research)
Diabetic nephropathy (DN) is a leading cause of kidney morbidity. Despite the multilayered complexity of the mechanisms involved in the pathogenesis of DN, the conventional treatment is limited to just a few drug classes fraught with the risk of adverse events, including the progression of renal dysfunction. Phytoceuticals offer a promising alternative as they act on the many-sidedness of DN pathophysiology, multitargeting its intricacies. This paper offers a review of the mechanisms underlying the protective action of these phytoagents, including boosting the antioxidant capabilities, suppression of inflammation, averting the proliferative and sclerosing/fibrosing events. The pathogenesis of DN is viewed as a continuum going from the original offense, high glucose, through the noxious products it generates (advanced glycation end-products, products of oxidative and nitrosative stress) and the signaling chains consequently brought into action, to the harmful mediators of inflammation, sclerosis, and proliferation that eventually lead to DN, despite the countervailing attempts of the protective mechanisms. Special attention was given to the various pathways involved, pointing out the ability of the phytoagents to hinder the deleterious ones (especially those leading to, driven by, or associated with TGF-β activation, SREBP, Smad, MAPK, PKC, NF-κB, NLRP3 inflammasome, and caspase), to promote the protective ones (PPAR-α, PPAR-γ, EP4/Gs/AC/cAMP, Nrf2, AMPK, and SIRT1), and to favorably modulate those with potentially dual effect (PI3K/Akt). Many phytomedicines have emerged as potentially useful out of in vitro and in vivo studies, but the scarcity of human trials seriously undermines their usage in the current clinical practice—an issue that stringently needs to be addressed.